2010
DOI: 10.1007/s10072-010-0356-8
|View full text |Cite
|
Sign up to set email alerts
|

Three years of experience: the Italian registry and safety data update

Abstract: At the end of 2006, a pharmacovigilance program on natalizumab was settled by the Italian Pharmaceutical Agency, and on January 2007, multiple sclerosis patients poorly responding to the immunomodulating therapies or with an aggressive clinical form of disease from onset initiated to be registered and to receive the medication. On February 2010, almost 3,000 cases have been treated with natalizumab. The drop-out rate is 10%. Almost 800 cases received cycles of natalizumab for more than 18 months. One case of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 3 publications
1
21
3
2
Order By: Relevance
“…The proportion of patients who discontinued treatment was higher in our cohort than in other observational studies, but in the other studies not all patients had reached 2 full years of treatment, thus inducing an underestimation of discontinuation [4][5][6][7][8][9]. The reasons for discontinuing natalizumab were numerous in our study, as in other studies, but the classification and distribution could be relatively different, thus making any comparison difficult.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The proportion of patients who discontinued treatment was higher in our cohort than in other observational studies, but in the other studies not all patients had reached 2 full years of treatment, thus inducing an underestimation of discontinuation [4][5][6][7][8][9]. The reasons for discontinuing natalizumab were numerous in our study, as in other studies, but the classification and distribution could be relatively different, thus making any comparison difficult.…”
Section: Discussioncontrasting
confidence: 61%
“…We observed a better radiological response and a worse clinical response than that reported in the AFFIRM cohort. As in all observational post-marketing studies [4][5][6][7][8][9], our population of patients treated with natalizumab had a higher disease duration, baseline EDSS, ARR and more often previously been treated by immunomodulatory drugs than in AFFIRM study [1]. Nevertheless, our cohort had a shorter disease duration, higher baseline EDSS and similar ARR compared to other post-marketing studies.…”
Section: Discussioncontrasting
confidence: 34%
“…Most published studies on this topic are descriptive [5,7,10-16]. Few research papers have attempted to correlate baseline data with outcome towards prediction of treatment response, and results are not always consistent between studies, possibly due to the methodological biases that might affect uncontrolled longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore comforting that a number of observational studies have confirmed the efficacy of natalizumab reported in clinical trials (Table 1). The duration of treatment was up to 50 months in one case [Fernández et al 2012] and three studies included more than 1000 patients [Fernández et al 2012;Mancardi et al 2011;Piehl et al 2011]. In these studies, the baseline EDSS ranged from 3.1 to 4.0 compared with 2.53 in the AFFIRM trial.…”
Section: Natalizumab In Clinical Practicementioning
confidence: 99%